PENGARUH KEPERCAYAAN, KEPUASAN, DAN KUALITAS PELAYANAN TERHADAP MINAT PEMBELIAN KEMBALI OLX INDONESIA - Abraham Febrian Widodo; Daniel Joel Immanuel Kairupan (Jurnal Akuntansi Dan Manajemen, 2022)
This study aims to test the trust, satisfaction, and service quality of OLX Indonesia's repurchase intention. The sample selection method used in this study is simple random sampling with respondents using OLX criteria. The type of data used in this study is primary data obtained by using a questionnaire via google form with a total of 100 respondents. The results of this study show that trust (X1) has no significant effect on the repurchase interest of OLX Indonesia, satisfaction (X2) has a significant effect on the repurchase interest of OLX Indonesia, service quality (X3) has a significant effect on the repurchase interest of OLX Indonesia